Validity and Reliability of the Turkish Version of the Mental Health Literacy Scale in a General Population - Gülle, Buğra Taygun; Karabey, Selma (The European Research Journal, 2026)
Objectives: This study examines the validity and reliability of the Turkish version of the Mental Health Literacy Scale (T-MHLS) in a general population sample. Mental health literacy (MHL) is essential for recognizing and addressing mental health disorders; however, limited knowledge in this area contributes to underreported cases and untreated conditions. Methods: The study was conducted using face-to-face interviews, adapting the T-MHLS from the original MHLS. Exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA) were conducted to validate the structure of the scale. The sample size and data collection method ensured robust data, while validity and reliability analyses followed established psychometric protocols. Results: Data were collected from 401 participants, and items with low factor loadings were removed, resulting in a final five-factor structure with 30 items, explaining 58.7% of the variance. Known-group validity analysis revealed that factors such as gender, marital status, education level, income perception, and personal or familial experiences with mental illness significantly influenced MHL scores. The Cronbach’s alpha for the final scale was 0.861. Conclusions: The T-MHLS is shown to be a valid and reliable tool for assessing mental health literacy in Turkey. This scale is recommended for use in future studies involving various demographic groups to effectively measure MHL levels.